Trends towards regionalism in the world economy: A contribution to a new international economic order? - Detlef Lorenz (Intereconomics, 1989)
The world economy has for some time been characterised by a growing generalised trend towards regionalism. This is often considered to be on a par with the formation of blocs, fragmentation of the trading system and a relapse into the disastrous conditions of the thirties. However, if regionalism is understood not as a defensive or aggressive policy of bloc building, as in the thirties, but as a regional grouping that is open towards the world economy, it appears to have something to offer as an alternative to the old international economic order.
Keywords: 330; International Trade